Generalized impedance control of a SCARA robot for assembly tasks - Meng, Yan. (2010)
This thesis describes the control of a robotic system for an assembly task of inserting a printed circuit board (PCB) horizontally into an edge connector socket using a selective compliance assembly robot arm (SCARA) robot. The insertion task involves compliant manipulation in which a substantial force is needed to accomplish the insertion operation. Due to dynamic constraints from the environment, this task is quite demanding and is adopted in the research as a common test-bed to evaluate the performance of various proposed control schemes. The purpose is to identify an effective control technique for this application and hope that the findings can be extended to other assembly tasks of similar nature.